Mechanical Properties of Al-7075/ Fly ash particle reinforced metal matrix composites (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Metal matrix composites (MMCs) offer much higher specific strength, specific modulus, damping capacity, and wear resistance when compared to unreinforced alloys. Composites with low density and low cost reinforcements are gaining popularity. Among the numerous compositions used, fly ash is the most cost-effective and low-density reinforcement readily available as a solid waste byproduct of coal combustion in thermal power plants in substantial quantities. As a result, it is expected that composites reinforced with fly ash would overcome the cost barrier for broad usage in vehicle and small engine applications. .As a result, the incorporation of fly ash particles into aluminium alloy is expected to inspire yet another application of this low-cost waste by-product, while also having the ability to save energy-intensive aluminium, decreasing the cost of aluminium items. Particulate reinforced aluminium matrix composites are gaining popularity due to their low cost and advantages such as isotropic properties and the possibility of secondary processing, which allows for the production of additional components. The present research focuses on exploiting widely available industrial waste fly-ash by dispersing it in aluminium to create composites using the stir casting technique